An updated management approach of Pompe disease patients with high-sustained anti-rhGAA IgG antibody titers: experience with bortezomib-based immunomodulation - Desai, Ankit K.; Shrivastava, Garima; Grant, Christina L.; Wang, Raymond Y.; Burt, Trevor D.; Kishnani, Priya S. (Frontiers in Immunology, 2024)
Introduction High sustained anti-rhGAA antibody titers (HSAT; ≥12,800) are directly linked to reduced efficacy of enzyme replacement therapy (ERT) and subsequent clinical deterioration in infantile-onset Pompe disease (IOPD). We have previously demonstrated the safety and effectiveness of a bortezomib-based immune-tolerance induction (ITI) regimen (bortezomib, rituximab, methotrexate, and IVIG) in eliminating HSAT. Methods Here, we describe two IOPD cases (patients 6 and 8) who developed HSAT at 8 and 10 weeks on ERT despite transient low-dose methotrexate ITI administration in the ERT-naïve setting and were treated with a bortezomib-based ITI regimen, and we compare their courses to a series of six historical patients (patients 1-5, and 7) with a similar presentation who exemplify our evolving approach to treatment. Results In total, patients 6 and 8 received 16 and 8 doses of bortezomib (4 doses=1 cycle) respectively reducing titers from 25,600 to seronegative, but differences in the course of their therapy were instructive regarding the optimal approach to initial treatment of HSAT; specifically, patient 6 was treated initially with only a single course of bortezomib rescue therapy, while patient 8 received two back-to-back courses. Patient 8 received IVIG therapy throughout the immunosuppression whereas patient 6 received IVIG therapy and was switched to subcutaneous IgG replacement. Patient 6 had a transient reduction in anti-rhGAA antibodies, after receiving a single initial cycle of bortezomib, but had a recurrence of high anti-rhGAA antibody titer after 160 weeks that required 3 additional cycles of bortezomib to ultimately achieve tolerance. In contrast, patient 8 achieved tolerance after being given two consecutive cycles of bortezomib during their initial treatment and had B cell recovery by week 54. Since the reduction in anti-rhGAA antibodies, both patients are doing well clinically, and have decreasing ALT, AST, and CK. No major infections leading to interruption of treatment were observed in either patient. The bortezomib-based ITI was safe and well-tolerated, and patients continue to receive ERT at 40 mg/kg/week. Discussion These case studies and our previous experience suggest that to achieve an effective reduction of anti-rhGAA antibodies in the setting of HSAT, bortezomib should be initiated at the earliest sign of high anti-rhGAA antibodies with a minimum of two consecutive cycles as shown in the case of patient 8. It is important to note that, despite initiation of ERT at age 2.3 weeks, patient 8 quickly developed HSAT. We recommend close monitoring of anti-rhGAA antibodies and early intervention with ITI as soon as significantly elevated anti-rhGAA antibody titers are noted.